Critical mountaineering decisions: technology, expertise and subjective risk in adventurous leisure. Issue 5 (2nd September 2020) - Groves, Matthew R.; Varley, Peter J.
ABSTRACT: Humans have developed strategies of varying complexity to augment their probability of survival and success in complex environments. In contemporary outdoor adventure scenarios, advances in knowledge, training and technology have been adopted to make us safer, or make us feel safer. Avalanche-prone terrain is one such complex environment where uncertainty is key. A small-sample pilot study was conducted during a 3-year trial of mandatory avalanche transceiver, shovel and probe use at Glenmore Lodge, sportscotland National Outdoor Training Centre. The perceived effects that the equipment might have on participants' risk perceptions and risk-taking behaviour were investigated through semi-structured interviews. Patterns of avalanche risk perception and relationship with the safety equipment varied strongly between expertise levels, and a discrepancy between declared risk behaviour and action, demonstrations of optimistic bias and defensive denial were evident. Wider implications are suggested regarding subjective relationships with both risk and technology in adventure settings and, in our leisure more generally.